IMPLEMENTASI MBKM TERHADAP PROSES PEMBELAJARAN KOLABORATIF DI UNIVERSITAS MEGA BUANA PALOPO - Indra Amanah Indra Amanah AN; Yuniar Dwi Yanti Yuniar Dwi Yanti; Arianto Dangkeng Arianto Dangkeng (LPPM STIKES BINA GENERASI POLEWALI MANDAR, 2022)
The learning process in the Merdeka Campus is one of the most essential manifestations of student centered learning. Learning at the Merdeka Campus is a challenge and opportunity to develop innovation, provide creativity, capacity, personality, and student needs, as well as develop independence in finding and discovering knowledge through realities and field dynamics such as needs, real problems, social interaction, collaboration, self-management, performance , targets and performance. Through the Merdeka Learning program that is well designed and implemented, students' hard skills and soft skills will be formed strongly. Methods: The type of research used is a mixed method, between qualitative and quantitative. This research is located at Mega Buana University, Palopo. The research was carried out in December 2021. The research population was all leaders of Mega Buana Palopo University, Lecturers, Tendik and Students of Mega Buana Palopo University. This study was conducted on the entire population. Data was collected through focus group discussions, interviews and using a questionnaire. Discussion Results: Mega Buana Palopo University has run several programs that support the MBKM program, such as student apprenticeships, independent student projects, KKN, Mega Buana University can optimize the collaborative learning process for students, Mega Buana Palopo University can run MBKM programs optimally starting from Internal PT, Mega Buana University can increase link and match with industry by making Industrial Practitioners as teaching lecturers as well as increasing student apprenticeships according to the industrial sector